Generation sex the interaction between adolescents and sexual media in the 21st century - Cariño, Alvin M.
Adolescence is a crucial stage for self-discovery, sexual development, and sexual exploration. Despite the fact that some aspects of adolescents' sexual behavior are natural, they are ingrained in them through their environment. In modern society, the media acts as the primary sexual socialization, and adolescents are vulnerable to its impact as they find it difficult to evaluate media messages critically and make judgments based on potential future results. Therefore, there is a need for a comprehensive study between adolescents and the sexual media to further understand how and why adolescents interact with sexual media, and how sexual media, in turn, influences adolescents? sexual attitudes and behaviors. Using narrative analysis of qualitative research and the Media Practice Model of Jeanne R. Stelle and Jane D. Brown as a guiding theory, the study was able to explore the interaction between adolescents and the sexual media. The study confirms that adolescents' understanding about sex primarily comes from the media, particularly the new media. It indicated that the culmination of media over-saturation has produced a distorted understanding of sexuality that appears to mostly have negative effects on adolescents, but surprisingly, also presents positive implications on adolescents' awareness and self-control. The interaction between adolescents and sexual media also emphasizes that what adolescents learn from the sexual media influences their future consumption and exploration of sexual information.